1991
DOI: 10.1063/1.460056
|View full text |Cite
|
Sign up to set email alerts
|

Nonstatistical CO product distributions from the hot H-atom reaction, H+CO2→OH+CO

Abstract: A quasiclassical trajectory study of the OH+CO reaction J. Chem. Phys. 95, 1635 (1991); 10.1063/1.461076 Investigation of OHH2 and OHCO reactions using argonsensitized pulse radiolysisThe hot H-atom reaction, H + e0 2 ..... OH + eo is investigated under several initial conditions designed to vary the angular momentum of the CO 2 reactant. The translationally hot H atoms are produced by photodissociating H 2 S at 193 nm, resulting in a reaction exoergicity of -120 kJ mol -1. The internal energy in the eo produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…(The phase space theoretical population distributions were calculated using a maximum orbital angular momentum L max ∼ 100 ℏ, but were found insensitive to L max in range ∼10−100 ℏ). Since f t = 1 − (where is the fraction of the energy available for the CO coproducts of OH( v ‘ = 0, N ‘ = 1) which is released into CO internal excitation), the data reveal that the pair-correlated CO internal energy distributions at both collision energies are considerably colder than phase space theory prediction, a conclusion which is in general accord with the (OH state-averaged, global) CO internal state populations determined by Rice and Baronavski . The results are also consistent with our previous measurements of the internal energy distribution of the CO coproducts of OH( v ‘ = 0, N ‘ = 5, A ‘/ A ‘‘), generated via reaction 1 at 2.5 eV …”
Section: Resultssupporting
confidence: 89%
“…(The phase space theoretical population distributions were calculated using a maximum orbital angular momentum L max ∼ 100 ℏ, but were found insensitive to L max in range ∼10−100 ℏ). Since f t = 1 − (where is the fraction of the energy available for the CO coproducts of OH( v ‘ = 0, N ‘ = 1) which is released into CO internal excitation), the data reveal that the pair-correlated CO internal energy distributions at both collision energies are considerably colder than phase space theory prediction, a conclusion which is in general accord with the (OH state-averaged, global) CO internal state populations determined by Rice and Baronavski . The results are also consistent with our previous measurements of the internal energy distribution of the CO coproducts of OH( v ‘ = 0, N ‘ = 5, A ‘/ A ‘‘), generated via reaction 1 at 2.5 eV …”
Section: Resultssupporting
confidence: 89%
“…We have also calculated the rotational state distributions of CO with thermally prepared CO 2 (data not shown) and found no significant differences, in contrast to what observed by Rice and Baronavski. 15 In addition, the calculated CO rotational state distributions on the ground and first excited CO vibrational channels are quite similar. This is consistent with the observation of Nickolaisen et al, 16 but differ from the report of Rice and Baronavski, 15 who observed high rotational excitation for v = 1.…”
Section: Final State Distributionsmentioning
confidence: 72%
“…For instance, the latest QCT study 34 on the Lakin-Troya-Schatz-Harding (LTSH) PES (Ref. 30) failed to reproduce the monotonically increasing excitation function observed in the experiment of Hoffmann et al 14 In addition, this theoretical study predicted much hotter CO rotational state distributions than observed experimentally by Rice and Baronavski 15 and by Nicholaisen et al 16 A key issue in reaction dynamics is the accuracy of the underlying PES. The HOCO PES is quite complex, involving two bottlenecks along its main reaction pathway, as shown in Fig.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations